1999
DOI: 10.1016/s0735-1097(99)00255-7
|View full text |Cite
|
Sign up to set email alerts
|

Sinus node function and ventricular repolarization during exercise stress test in long QT syndrome patients with KvLQT1 and HERG potassium channel defects

Abstract: LQT1 is associated with diminished chronotropic response and exaggerated prolongation of QT interval after exercise. LQT2 patients differ from LQT1 patients by having marked QT interval shortening and normal heart rate response to exercise. Observing QT duration during recovery enhances the clinical diagnosis of these LQTS types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
98
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 24 publications
17
98
0
4
Order By: Relevance
“…However, no prior data demonstrate a clear primary autonomic abnormality in patients with LQTS. Examination of earlier studies documenting resting heart rate suggest a tendency toward slower heart rate in patients with LQTS, 6 although this has not been previously confirmed. Our data suggest that the slower heart rate observed previously in children Ͻ3 years of age with LQTS 16 seems to be present even in adults, when these measurements are obtained in resting undisturbed conditions and compared with closely matched control subjects.…”
Section: Discussionmentioning
confidence: 88%
“…However, no prior data demonstrate a clear primary autonomic abnormality in patients with LQTS. Examination of earlier studies documenting resting heart rate suggest a tendency toward slower heart rate in patients with LQTS, 6 although this has not been previously confirmed. Our data suggest that the slower heart rate observed previously in children Ͻ3 years of age with LQTS 16 seems to be present even in adults, when these measurements are obtained in resting undisturbed conditions and compared with closely matched control subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Western blot analyses of WT hERG overexpression in several systems, including HEK-293 cells, have shown two protein bands at 135 kDa (immature) and 155 kDa (mature) that represent posttranslational core and complex glycosylation of hERG protein, respectively (2,15,19,45). We next transfected the missense mutations, G601S and N470D hERG (12,16,36), that form trafficking-deficient channel proteins when studied in noncardiac mammalian systems (3,16,45). Western blot analysis in the cardiomyocytes showed that G601S and N470D hERG generate 135-kDa protein bands but only weak or no 155-kDa protein bands, indicating that for control conditions these two mutations generate immature protein that then does not undergo normal Golgi processing to the mature protein.…”
Section: Resultsmentioning
confidence: 99%
“…50 Both of these techniques can aid clinicians in distinguishing LQT1 from LQT2 patients. Studies have also shown differential response of LQT1, 2, and 3 patients to epinephrine infusion.…”
Section: Phenotypic Ascertainment: Other Diagnostic Testsmentioning
confidence: 99%